2010
DOI: 10.1007/s10661-010-1659-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton distribution across the southeast Adriatic continental and shelf slope to the west of Albania (spring aspect)

Abstract: We present the first insight to the oceanography of the southeastern Adriatic Sea, where coastal water influenced by Albanian rivers comes into contact with the inflowing oligotrophic Eastern Adriatic Current (Ionian Surface Water and Levantine Intermediate Water). A distinct plankton distribution was observed on each side of the shelf break hydrographic boundary in May 2009, during gradual warming of the surface waters. The prochlorophytes accumulated along the nutricline above the shelf and continental slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The same, i.e. fast consumption of nutrients and restriction of primary production to the coast, has been found around the eastern Adriatic freshwater inputs (Marini et al, 2010;Ninčević Gladan et al, 2010;Viličić et al, 2011). By contrast, the open Adriatic water nutrient load is mostly controlled by the inflowing waters coming from the Ionian Sea (Šolić et al, 2008).…”
Section: Introductionmentioning
confidence: 74%
“…The same, i.e. fast consumption of nutrients and restriction of primary production to the coast, has been found around the eastern Adriatic freshwater inputs (Marini et al, 2010;Ninčević Gladan et al, 2010;Viličić et al, 2011). By contrast, the open Adriatic water nutrient load is mostly controlled by the inflowing waters coming from the Ionian Sea (Šolić et al, 2008).…”
Section: Introductionmentioning
confidence: 74%
“…For the southern Adriatic Viličić et al [16] reported a checklist of the phytoplankton community and showed presence of the phytoplankton species. In the southeastern Adriatic, Viličić et al [17] presented influence of Albanian rivers on the nutrients distribution and distribution of phytoplankton and showed dominance of diatoms such as Chaetoceros species (C. circinalis, C. diversus). Caroppo et al [18] presented phytoplankton seasonality in the south-western part of the Adriatic and found that phytoplankton densities show specific oligotrophic water.…”
Section: Introductionmentioning
confidence: 99%
“…While phytoplankton can directly absorb and use DIP, the absorption rate of organic phosphorus is low. Some phytoplankton may only take up organic phosphorus when inorganic phosphorus is depleted (VILIČIĆ, et al, 2011), and phosphorus de ciency can be directly related to growth and reproduction of phytoplankton and species succession. Under long-term phosphorus limitation conditions, phytoplankton can reduce cellular demand for phosphorus by slowing cell growth (Brembu, et al, 2017;Teikari, et al, 2015;Mohlin and Wulff, 2009), and some phytoplankton also slow phosphorus limitation by increasing cell volume (Li, et al, 2016;Zhang, et al, 2018).…”
Section: Correlations Between Environmental Variables and Phytoplankt...mentioning
confidence: 99%